2019
DOI: 10.21037/tlcr.2019.03.10
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of EGFR mutation status in tissue and plasma cell-free DNA detected by ADx-ARMS in advanced lung adenocarcinoma patients

Abstract: Background: Previous studies have shown that there are different methods used to detect the epidermal growth factor receptor (EGFR) mutation status in plasma cell-free DNA (cfDNA) for advanced lung adenocarcinoma patients including the ADx-Amplification Refractory Mutation System (ADx-ARMS). We explored the performance of the ADx-ARMS in detecting the EGFR mutations in cfDNA. Methods: This prospective cohort study enrolled patients who presented with advanced (stage IIIb/IV) lung adenocarcinoma. EGFR mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…After exclusion of studies, a total of 40 studies were finally included in our systematic review and meta-analysis. 2463…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion of studies, a total of 40 studies were finally included in our systematic review and meta-analysis. 2463…”
Section: Resultsmentioning
confidence: 99%
“…1). It is easy to see that these studies used the column-based method in cfDNA extraction [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] that lead to the low-yield of cfDNA and low sensitivity [9]. In the study, we also found that smoking habits influence the presence of EGFR mutations in plasma (Additional file 2: Table S2) and thus affect the sensitivity of the test ( Table 1).…”
Section: Discussionmentioning
confidence: 82%
“…It is worth noting that EGFR mutations in plasma are detected by the scorpion ARMS method that has a lower limit of detection than the pyrosequencing method (≈ 5%) [13]. We performed a literature review and noted that the false-negative phenomenon also is observed in other studies used scorpion ARMS method [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], dPCR [5,6,29], and even ultra-deep sequencing methods [2][3][4]30]. Therefore, the EGFR plasma sensitivity might be affected by the other factors besides the technique influences.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 studies were finally included in the meta-analysis after reading through the full text. [ 17 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 ] The flowchart is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%